Cover Image. (15th July 2021) - Li, Yuan; Li, Bingwei; Wang, Bing; Liu, Mingming; Zhang, Xiaoyan; Li, Ailing; Zhang, Jian; Zhang, Honggang; Xiu, Ruijuan
Abstract : The cover image is based on the Original Article Integrated Pancreatic Microcirculation Profiles of Streptozotocin‐Induced and Insulin‐Administrated Type 1 Diabetes Mellitus by Mingming Liu et al., https://doi.org/10.1111/micc.12691 .